2017
DOI: 10.1007/s00253-017-8117-8
|View full text |Cite
|
Sign up to set email alerts
|

LetR is a TetR family transcription factor from Lysobacter controlling antifungal antibiotic biosynthesis

Abstract: Heat-stable antifungal factor (HSAF) is a newly identified and broad-spectrum antifungal antibiotic from Lysobacter enzymogenes, a ubiquitous environmental proteobacterium. Yet, the regulatory mechanism for HSAF biosynthesis in L. enzymogenes remains poorly understood. Here, we report the identification of a TetR-family protein Le1552 (LetR) from L. enzymogenes strain OH11 that is involved in transcriptional repression of HSAF production. Bacterial one-hybrid and gel mobility shift assays show that LetR direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…RpfG affects HSAF production at the level of gene expression ( 26 ), therefore we expected LchP to also affect gene expression. To test this prediction, we measured, via quantitative RT-PCR (qRT-PCR), mRNA levels of lafB , the first gene in the HSAF biosynthesis operon ( 17 ). We found the level of the lafB transcript in the lchP mutant to be decreased by >2-fold, compared to the wild type (Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RpfG affects HSAF production at the level of gene expression ( 26 ), therefore we expected LchP to also affect gene expression. To test this prediction, we measured, via quantitative RT-PCR (qRT-PCR), mRNA levels of lafB , the first gene in the HSAF biosynthesis operon ( 17 ). We found the level of the lafB transcript in the lchP mutant to be decreased by >2-fold, compared to the wild type (Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Lysobacter enzymogenes is a nonpathogenic, plant-associated gammaproteobacterium known for synthesis of the antifungal antibiotic Heat-Stable Antifungal Factor, HSAF ( 11–14 ), which makes it an attractive biological control agent for fungal diseases of agriculturally important plants ( 11 , 12 , 15 ). Therefore, identifying genes and growth conditions that regulate HSAF production has been of significant interest ( 16 , 17 ). Our earlier work revealed that elevated intracellular c-di-GMP levels are detrimental for HSAF production due to lower HSAF biosynthesis gene expression ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…This transcriptional factor binds to a 150‐bp region located upstream of the pks/nrps gene, representing the potential promoter of the pks/nrps gene (Wang et al . ).…”
Section: The Regulatory Network In Lysobacter Enzymogenesmentioning
confidence: 97%
“…Moreover, HSAF is synthesized by an operon containing more than ten genes in L. enzymogens , wherein lafB (described initially as hsaf pks/nrps ), the first gene of this operon, encodes a hybrid polyketide synthase/nonribosomal peptide synthetase that catalyses the linkage of one ornithine to two polyketide chains during HSAF assembly. This mechanism is unique among most known biosynthesis reactions of natural bacterial products (Chen et al , ; Lou et al , ; Wang et al , ). Together, these unique features render HSAF an ideal candidate for the development of fungicides for crop protection.…”
Section: Introductionmentioning
confidence: 99%